Manipulation of EGFR-Induced Signaling for the Recruitment of Quiescent Neural Stem Cells in the Adult Mouse Forebrain - Cochard, Loïc M.; Levros, Louis-Charles; Joppé, Sandra E.; Pratesi, Federico; Aumont, Anne; Fernandes, Karl J. L. (Frontiers in Neuroscience, 2021)
The ventricular-subventricular zone (V-SVZ) is the principal neurogenic niche in the adult mammalian forebrain. Neural stem/progenitor cell (NSPC) activity within the V-SVZ is controlled by numerous extrinsic factors, whose downstream effects on NSPC proliferation, survival and differentiation are transduced via a limited number of intracellular signalling pathways. Here, we investigated the relationship between age-related changes in NSPC output and activity of signalling pathways downstream of the epidermal growth factor receptor (EGFR), a major regulator of NSPC activity. Biochemical experiments indicated that age-related decline of NSPC activity in vivo is accompanied by selective deficits amongst various EGFR-induced signal pathways within the V-SVZ niche. Pharmacological loss-of-function signalling experiments with cultured NSPCs revealed both overlap and selectivity in the biological functions modulated by the EGFR-induced PI3K/AKT, MEK/ERK and mTOR signalling modules. Specifically, while all three modules promoted EGFR-mediated NSPC proliferation, only mTOR contributed to NSPC survival and only MEK/ERK repressed NSPC differentiation. Using a gain-of-function in vivo genetic approach, we electroporated a constitutively active EGFR construct into a subpopulation of quiescent, EGFR-negative neural stem cells (qNSCs); this ectopic activation of EGFR signalling enabled qNSCs to divide in 3-month-old early adult mice, but not in mice at middle-age or carrying familial Alzheimer disease mutations. Thus, i) individual EGFR-induced signalling pathways have dissociable effects on NSPC proliferation, survival and differentiation, ii) activation of EGFR signalling is sufficient to stimulate qNSC cell cycle entry during early adulthood, and iii) the proliferative effects of EGFR-induced signalling are dominantly overridden by anti-proliferative signals associated with aging and Alzheimer’s disease.